Factors affecting job selection preferences among International Business Students in Universiti Teknologi MARA (UiTM) Malacca City Campus / Siti Badariah Masuri - Masuri, Siti Badariah (2015)
Graduates are an integral part to today's employment market. Career choice is a complex decision for students since it determines the kind of profession that they intend to pursue in life. In Malaysia, undergraduates have to make career choices before their graduation. The purpose of this study is to examine the factors affecting job selection preferences among International Business Students of Universiti Teknologi MARA (UiTM), Malacca City Campus that consider important in selecting their first job after graduation. In this present study, career development, salary and benefits, employer reputation, working environment, and job security have been chosen as the independent variables. To investigate the job selection preferences, 150 of undergraduate International Business students were surveyed. The data collected is analyzed using SPSS software. The research findings showed that two factors, which are Working Environment and Job Security have significant relationship with job preferences, while the rest of the factors are not significantly related to dependent variable. The results of this study are expected to bring insights to corporate recruiters such that they can attract more competent candidates that appropriately match the student's preferences. This research could also be used not only by business students but also students from different fields of study to help them to understand better in choosing career. Therefore, the present study will be able to contribute to the local research by serving as a references for local researchers in their future studies.